Effect of a plant versus animal based diet on lipid profile of yoga practicing medical students: a pilot study - Meetali, Sanasam; H. C., Shashikiran; Shetty, Prashanth; Prasad, Ganesh; K. K., Chandrakanth (International Journal of Research in Medical Sciences, 2018)
Background: Foods play an important role in human health. An excess accumulation of cholesterol in the body is one of the main causes of cardio vascular disease, hypertension, type 2 diabetes mellitus, dyslipidemia and mortality. In the interests of food safety and public health, plants and their compounds are now re-emerging as an alternative approach to treat gastrointestinal diseases. The present study was designed to discuss changes in blood cholesterol levels after the consumption of animal based (non vegetarian) and plant based (vegetarian) food on yoga practising medical students. Methods: Of 81 subjects, a total of 60 subjects within the age group 18 to 22 years were selected for the study and were divided into two groups, non-vegetarian diet group (group A; n=30) and vegetarian diet group (group B; n=30). Subjects in the group A were given a non vegetarian diet and group B a vegetarian diet for a period of 10 days. Assessments were done at baseline and after 10 days. Results: There were no statistically significant changes seen in the lipid profiles of group B and group A after the application of a paired t test. In this study the mean value of total cholesterol, serum triglyceride, serum LDL and serum VLDL were found to be slightly higher in vegetarian group than the non-vegetarian group. Mean value of serum HDL was found to be higher in non-vegetarian group than the vegetarian. Conclusions: The present study concludes that there are more changes in the pre and post lipid profile assessments of the vegetarian group in comparison to the non-vegetarian group.